2020
DOI: 10.34172/ajcmi.2020.08
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chlamydia pneumoniae Infection in Patients With Multiple Sclerosis: A Case-Control Study

Abstract: Background Multiple sclerosis (MS) is a chronic autoimmune disorder of the central nervous system (CNS) with myelin destructions induced by the immune system (1). The clinical symptoms of MS are highly variable and can include impaired vision and abnormalities in the motor and coordination systems (2). Four general forms for this disease include primary progressive, secondary progressive, relapsing-remitting, and progressive relapsing (3). The disease typically occurs at the age of 18 to 40 and almost in women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…paratuberculosis, which has homology with the C region of the gamma chain of the T cell receptor, in MS [ 27 ]. Some studies show a correlation between the incidence of MS and the presence of antibodies to C. pneumoniae, but the exact role of these antibodies in pathogenesis of the disease remains unclear [ 28 , 29 ]. In vivo studies have shown that microbiota from MS twins transplanted to transgenic mice with the T cell receptor specific for myelin oligodendrocyte glycoprotein (MOG), caused a higher level of autoimmunity than the microbiota obtained from healthy twins [ 30 ].…”
Section: Endogenous and Exogenous Factors Affecting The Developmenmentioning
confidence: 99%
“…paratuberculosis, which has homology with the C region of the gamma chain of the T cell receptor, in MS [ 27 ]. Some studies show a correlation between the incidence of MS and the presence of antibodies to C. pneumoniae, but the exact role of these antibodies in pathogenesis of the disease remains unclear [ 28 , 29 ]. In vivo studies have shown that microbiota from MS twins transplanted to transgenic mice with the T cell receptor specific for myelin oligodendrocyte glycoprotein (MOG), caused a higher level of autoimmunity than the microbiota obtained from healthy twins [ 30 ].…”
Section: Endogenous and Exogenous Factors Affecting The Developmenmentioning
confidence: 99%
“…It usually infects people while they are school-aged children or young adults for the first time. Reinfection, on the other hand, is more common among the elderly [ 9 ]. C. pneumoniae can infect a range of different cell types.…”
Section: Introductionmentioning
confidence: 99%